TEST-CHECKING AND THE POISSON DISTRIBUTION-A FURTHER COMMENT. - Cyert, R. M. (The Accounting Review, 1957)
The article presents a comment on an article by Professor Marvin Tummins which discussed the manner in which the Poisson distribution can be used by auditors as an aid in test checking. After explaining how to read the table of the Poisson distribution, the author goes on to discuss the analysis of a random sample drawn from a lot under three sections, procedure for rejection of hypothesis, procedure for acceptance of hypothesis, and evaluation of indefinite sample result. Professor Tummins has performed a useful service in calling attention to the potential usefulness of the Poisson distribution for certain checking purposes. However, there are two comments that must be made of Tummins' approach. The first point is that Tummins seems to suggest that an acceptance sampling approach can be used in the actual auditing process. There are many problems raised by such a general approach to auditing, as has been amply demonstrated by R. J. Monteverde. The second comment, then, on the Tummins' paper is that the trial and error method that is suggested is much too awkward.